Virtual reality intervention as a support method during wound care and rehabilitation after burns: A systematic review and meta-analysis - Oliver Czech; Adam Wrzeciono; Ladislav Batalík; Joanna Szczepańska-Gieracha; Iwona Malicka; Sebastian Rutkowski (Elsevier, 2022)
Objective: This systematic review and meta-analysis aimed to analyze and synthesize the evidence on the effectiveness of virtual reality (VR) interventions in the prevention of pain, fear and anxiety during burn wound care procedures. Methods: In September and October 2021, PubMed, Scopus, Cochrane Library and Web of Science were searched for relevant randomized controlled and crossover studies. Two independent authors described the following inclusion criteria for the search: patients undergoing burn wound care with applied VR treatment compared to any other or non-VR intervention. From a total of 1171 records, 25 met the inclusion criteria. After full-text screening, seven publications were excluded. The risk of bias was assessed for 18 studies by two independent authors. RevMan 5.4 was used for the statistical analysis, meta-analysis and visual presentation of the results. Results: The meta-analysis showed a significant difference between VR treatment and standard care when analyzing pain outcome during wound care procedures (SMD = −0.49; 95% CI [−0.78, −0.15]; I2 = 41%) and in subgroup analysis when immersive VR was incorporated (SMD = −0.71; 95% CI [−1.07, −0.36]; I2 = 0%). No significant differences were found between VR treatment and standard care for range of motion outcome (SMD = 0.44; 95% CI [−0.23, 1.11]; I2 = 50%). Conclusions: VR seems to be an effective therapeutic support in burn wound care procedures for reducing pain. However, this systematic review and meta-analysis highlights the need for more research into the use of VR as a distraction method. Studies on larger groups using similar conditions can provide unequivocal evidence of the effectiveness of VR and enable the inclusion of such intervention in standard medical procedures.